Hepatic hematoma following endoscopic retrograde cholangiopancreatography: overview and case report - Cordova-Velazquez, Carlos A.; Reyes-Perez, Ana S.; García-Rivera, Hadassa H.; Regalado-Aquino, Adrian; Velázquez-García, José A. (International Journal of Research in Medical Sciences, 2023)
Endoscopic retrograde cholangiopancreatography (ERCP) is a procedure with a high risk of complications. Hepatic subcapsular hematoma is an infrequent complication, with few cases reported in the international literature. Treatment can be conservative with the patient under close surveillance in an intensive care unit and surgical management is reserved for failure of conservative treatment and cases with hemodynamic instability. We present a case of subcapsular and intraparenchymal hepatic hematoma in an adult male who presented sudden hemodynamic instability, associated with hemoglobin decrease, which required surgical management. The challenge in the therapeutic decision due to sudden hemodynamic instability is clearly demonstrated; therefore, there was a need for surgical treatment as the best measure of hemorrhage control. Conservative management should be reserved for hemodynamically stable patients and invasive management by interventional radiology or surgery for cases of acute abdomen associated with hemodynamic instability.